Prevalence and influencing factors of sexually transmitted diseases among men who have sex with men in Shandong province, 2022: a cross-sectional survey - Yingjie WANG; Meizhen LIAO; Xiaoyan ZHU; Na ZHANG; Lianzheng HAO; Guoyong WANG; Pengxiang HUANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the prevalence and influencing factors of sexually transmitted diseases (STD) among men who have sex with men (MSM) in Shandong province.MethodsUsing snow bowling, one site and online sampling methods, we recruited 4 416 MSM aged ≥ 16 years and having insertive oral or anal sex during past six months in 11 STD sentinel surveillance sites across Shandong province. Face-to-face interview with an unified national questionnaire was conducted among the participants during April - July 2022 to collect participants' information on sociodemographics, STD, STD-related sexual behaviors and intervention acceptances. Multivariate logistic regression were used to analyze influence factors of STD infection.ResultsSuffering from STD in the past one year was reported by 236 (5.34%) of the participants; of the STD sufferers, 51.3% (121) had syphilis and 23.7% (56/236) had Condyloma acuminatum (CA). Multivariate logistic regression showed that the participants with following characteristics were at an increased risk of STD infection: aged > 35 years (odds ratio [OR] = 1.697, 95% confidence interval [95%CI]: 1.046 - 2.755), with education of college or above (OR = 2.696, 95%CI: 1.131 - 6.425), having moderate cognition on the hazards of drug abuse (OR = 11.746, 95%CI: 1.523 - 90.568) or having higher cognition on the hazards of drug abuse (OR = 12.335, 95%CI: 1.645 - 92.496), having commercial homosexual behavior during last 6 months (OR = 2.273, 95%CI: 1.477 - 3.498), ever having group sex (OR = 1.693, 95%CI: 1.149 - 2.494), and ever taking pre-exposure prophylaxis (PrEP) (OR = 1.807, 95%CI: 1.100 - 2.967); while seeking homosexual partner via internet/dating software was a protective factor against STD infection (OR = 0.486, 95%CI: 0.271 - 0.871).ConclusionAmong MSM in Shandong province, the prevalence of STD, mainly syphilis and CA, is high and high-risk sexual behaviors and ever taking PrEP are risk factors for STD infection; the results suggest that more effective and targeted intervention measures should be developed among the MSM.